Perspectives on Electrostatics and Conformational Motions in Enzyme Catalysis - Hanoian, Philip (Acc Chem Res, 2015)
[Image: see text] Enzymes are essential for all living organisms, and their effectiveness as chemical catalysts has driven more than a half century of research seeking to understand the enormous rate enhancements they provide. Nevertheless, a complete understanding of the factors that govern the rate enhancements and selectivities of enzymes remains elusive, due to the extraordinary complexity and cooperativity that are the hallmarks of these biomolecules. We have used a combination of site-directed mutagenesis, pre-steady-state kinetics, X-ray crystallography, nuclear magnetic resonance (NMR), vibrational and fluorescence spectroscopies, resonance energy transfer, and computer simulations to study the implications of conformational motions and electrostatic interactions on enzyme catalysis in the enzyme dihydrofolate reductase (DHFR). We have demonstrated that modest equilibrium conformational changes are functionally related to the hydride transfer reaction. Results obtained for mutant DHFRs illustrated that reductions in hydride transfer rates are correlated with altered conformational motions, and analysis of the evolutionary history of DHFR indicated that mutations appear to have occurred to preserve both the hydride transfer rate and the associated conformational changes. More recent results suggested that differences in local electrostatic environments contribute to finely tuning the substrate pK(a) in the initial protonation step. Using a combination of primary and solvent kinetic isotope effects, we demonstrated that the reaction mechanism is consistent across a broad pH range, and computer simulations suggested that deprotonation of the active site Tyr100 may play a crucial role in substrate protonation at high pH. Site-specific incorporation of vibrational thiocyanate probes into the ecDHFR active site provided an experimental tool for interrogating these microenvironments and for investigating changes in electrostatics along the DHFR catalytic cycle. Complementary molecular dynamics simulations in conjunction with mixed quantum mechanical/molecular mechanical calculations accurately reproduced the vibrational frequency shifts in these probes and provided atomic-level insight into the residues influencing these changes. Our findings indicate that conformational and electrostatic changes are intimately related and functionally essential. This approach can be readily extended to the study of other enzyme systems to identify more general trends in the relationship between conformational fluctuations and electrostatic interactions. These results are relevant to researchers seeking to design novel enzymes as well as those seeking to develop therapeutic agents that function as enzyme inhibitors.